Thermally stable recyclable naphthalenediimide–siloxane polymers. Issue 1 (1st February 2016) - Prentice, Giles M.; Emmett, Liam M.; Zhu, Henghua; Kociok-Köhn, Gabriele; Pantoș, G. Dan
Abstract : We report here the synthesis and study of naphthalenediimide–siloxane polymers with high thermal stability. Two of the five polymers investigated could be developed into recyclable materials. We use solid-state 29 Si NMR to evaluate the degree of cross-linking and polymerisation in our materials.